The Facial Aging Process From the "Inside Out". (16th December 2020) - Swift, Arthur; Liew, Steven; Weinkle, Susan; Garcia, Julie K; Silberberg, Michael B
Abstract: The normal course of aging alters the harmonious, symmetrical, and balanced facial features found in youth, not only impacting physical attractiveness but also influencing self-esteem and causing miscommunication of affect based on facial miscues. With this evidence-based paper, the authors aim to provide a comprehensive overview of the latest research on the etiology and progression of facial aging by explaining the aging process from the "inside out, " that is, from the bony platform to the skin envelope. A general overview of the changes occurring within each of the main layers of the facial anatomy is presented, including facial skeleton remodeling, fat pad atrophy or repositioning, changes in muscle tone and thickness, and weakening and thinning of the skin. This is followed by an in-depth analysis of specific aging regions by facial thirds (upper, middle, and lower thirds). This review may help aesthetic physicians in the interpretation of the aging process and in prioritizing and rationalizing treatment decisions to establish harmonious facial balance in younger patients or to restore balance lost with age in older patients.